Micropropagation of White Palash tree (Butea monosperma (Lam.) Taub. Var. lutea (Witt.)). - D, Rathnaprabha; N, Muralikrishna; E, Raghu; V, yashodhara; A, Sadanandam (Journal of Phytology, 2017)
An efficient and reproducible protocol is established for rapid in vitro multiplication of an endangered, valuable medicinal plant, Butea monosperma (Lam.) Taub. Var. lutea, through cotyledonary nodes of mature seeds. Among various cytokinins tested, high frequency of direct shoot regeneration was induced on Murashige and skoog (MS) medium supplemented with BAP, which found to be more effective and showed optimal response at 2 mg/L with a maximum number of 8.35Â±0.32 multiple shoots per explant. Proliferation of shoots was established by repeated subculturing on to same regeneration medium with 2-3 weeks of time interval. Rooting of regenerated shoots was achieved after 3 weeks of culture on MS medium containing 1 mg/L IBA. In vitro raised plantlets were transferred to pots containing sterilized soil and vermiculate mixture in 1:1 ratio and then shifted to greenhouse. Well established plantlets exhibited 75% survival rate.